The Effects of Shifting to Transaction Value and Other Issues - Erlinda M. Medalla; Leah Panganiban-Castro (Philippine Institute for Development Studies (PIDS), 2000)
The study takes off from an earlier inquiry on the effects of HCV (home consumption value) valuation. This study is intended to assist policymakers as well as the private sector in their task of deciding whether to implement or postpone the adoption of the GATT Valuation Code (GVC) by January 1, 2000. Under the GVC, the dutiable base for imports is defined as the "transaction value"–i.e., "the price actually paid or payable for imported goods." The findings of the study support the argument that trade liberalization in the form of lower tariffs will reduce the incidence of underinvoicing.
Keywords: 330; transaction value; Außenhandelspreis; Zollpolitik; WTO-Recht; Philippinen